WAYS OF ENFORCING ADHERENCE TO REGIMENS IN PATIENTS WITH EATING DISORDERS - Premshila Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The discipline of health communication is one that crosses disciplinary lines and plays an important role in many other areas of study, such as public health, health care, global health, and community development. Health communication is a field of theory, research, and practise that studies and uses communication strategies, methods, programmes, and interventions as a means to inform and influence patients' decisions leading to positive health behaviour with the goal of enhanced health. The term "health communication" is used interchangeably with "health communication theory" and "health communication research." On the other hand, for the purposes of this investigation, the term "health communication" refers to the dialogue that takes place between the patient and the physician throughout the consultation process. Therefore, health communication, in the context of doctor-patient interaction, encompasses the ability to gather information that facilitates accurate diagnosis, to apply appropriate counselling skills that include basic empathy, to provide therapeutic instructions in a simple non-technical language so that they are easily comprehensible by the patient, and to establish a caring relationship with the patient.